Properties of Magnesium-Zinc Graphene Composites - Adzali, Nur Maizatul Shima; Nur Hidayah bt Ahmad Zaidi (Scientific Research Journal, 2025)
Magnesium (Mg) is a metal that is light in weight and well known for its high strength to various role in several biological processes, automotive components, alloys, and aerospace applications. The purpose of this study is to fabricate and determine the physical and mechanical properties of Mg Zn reinforced with graphene composites, with concern for enhancement of super strong material made of carbon atoms. The focus is on figuring out the effect of different percentages of graphene on the physical and mechanical properties of the composite. The aim of this research is to identify the best ratio that gives the hard and most durable Mg-Zn composite by using hardness test, Archimedes test, and XRD analysis. Five sample of Mg- Zn were fabricated with different percentages of graphene which were 0 wt.%, 1 wt.%, 3 wt.%, 5 wt.%, and 7 wt.%. All 5 samples were mixed in mixing drum for 30 minutes with speed of 200 revolutions per minute then the mixture is then placed in mold and compressed for 2 minutes under 8 tons of hydraulic pressure. Then the sample undergo sintering process where it was sintered for 2 hours in 350 °C. Then the sample were ground and polished before undergo hardness, Archimedes, and XRD test. Hardness result for Mg-Zn reinforced with graphene shows that the highest hardness value is with addition 3 wt.% of graphene (53.93 HRF), while the lowest reading is for 0 wt.% of graphene (26.67 HRF). For density result, maximum relative density (91.08%), was obtained from graphene percentage at 3 wt.%, while the lowest relative density (82.37%), was obtained from graphene percentage at 0 wt.%. From this research, sample with 3 wt.% of graphene shows better properties in term of hardness, porosity and XRD analysis. To conclude, the present work showed a successful fabrication of Mg-Zn composite added with graphene for application in biomedical sector and other sector.